2009
DOI: 10.1590/s1020-49892009000300005
|View full text |Cite
|
Sign up to set email alerts
|

Community beliefs and practices about dengue in Puerto Rico

Abstract: Suggested strategies to motivate residents' actions included working with government agencies to address structural problems that increase mosquito populations, improving access to information on garbage collection and water disposal through telephone hotlines, increasing publicity and information about dengue by mass media campaigns, and educating health professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
1
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 16 publications
5
69
1
13
Order By: Relevance
“…The significance of prevention and control may be attributed to the 2014 Chikungunya outbreak resulting in the Sint Eustatius population actually experiencing a mosquito-borne disease. In Puerto Rico, Perez et al [35,36] found that residents considered dengue an issue within the community mainly when people were aware of cases within the population.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of prevention and control may be attributed to the 2014 Chikungunya outbreak resulting in the Sint Eustatius population actually experiencing a mosquito-borne disease. In Puerto Rico, Perez et al [35,36] found that residents considered dengue an issue within the community mainly when people were aware of cases within the population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted with Puerto Rican residents found that a perceived link between flu-like illness and dengue has existed in the past due to the similarities of early disease symptoms. 8,9 In 2010, an island-wide educational campaign was launched to promote dengue prevention practices and encourage people to get the H1N1 vaccine. Juxtaposition of the perceived side effects from influenza vaccination and the message delivered by the educational campaign could have created more confusion among the public because they might have thought that the H1N1 vaccine protected against dengue.…”
Section: Discussionmentioning
confidence: 99%
“…7 Although community-based education programs have increased knowledge about vector control among the public, these programs have had limited success in changing behavior to prevent or control endemic dengue. 8,9 Studies in various countries have shown that use of pesticides has had little effect on reducing vector populations of Aedes aegypti. 7 Given the lack of effective tools for the primary prevention of dengue, there has been a major effort to develop safe and effective dengue vaccines as a tool to prevent this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Future campaigns should focus on educating and encouraging individuals and families to adopt such simple and inexpensive precautions, such as, use of insecticide treated bed nets and screening of homes. Furthermore, research Pérez-Guerra, Zielinski-Gutierrez, Vargas-Torres and Clark (2009) concluded that suggested strategies to motivate citizen action included working with government agencies to address structural issues that increase mosquito populations, improve access to information on garbage collection and drainage through telephone hotlines, improve publications and information about dengue through media mass campaigns, and educating healthprofessionals.…”
Section: Discussionmentioning
confidence: 99%